(3GdHMK GdYdej eagheg hCOhGJg hCSGdjHgs - (3YHjOGJ(B, (3PhbGfs; (3cGjO(B;(3YHO GdQMeGf(B, (3YHO GdMb(B;(3YOSs ((3YeGf(B:s (3OGQ GdacQ ddfTQ hGdJhRjY(B,s, 2005)
(3GdYde hGdHMK GdYdej(B-(3CSGSjGJ GdHMK GdYdej(B-(3COhGJ GdHMK GdYdej(B-(3CSGdjH GdHMK(B-(3cJGHI GdHMKs
Keywords: (3CSGdjH GdHMK GdYdejs; (3HMK Ydejs; (3Ydes